Ideology and Power in Presidential Speech: A Critical Analysis of Jokowi’s International Speeches - Waluyo, Gatot Hadi; Failasofah, Failasofah; Delita Sartika (Kajian Linguistik dan Sastra, 2025)
The relationship between language, ideology, and power has garnered the interest of numerous academics in the discipline of linguistics. Persuasive speech is a potent instrument employed by the government to govern and firmly establish its ideology. The objective of this study was to analyze Joko Widodo's international speeches in 2015 and 2022 to identify the Indonesian ideology values conveyed in his speeches and examine the expressions of these values that could serve as representations of the Indonesian ideology. The researcher employed qualitative research as the chosen research design, specifically emphasising critical discourse analysis. This investigation employed Van Dijk's textual methodology, which specifically examined the macrostructure and microstructure of the text. The research revealed that in both addresses, Joko Widodo articulated 8 principles that signified four concepts of Pancasila. The ideological ideals encompass care, unity, diligence, egalitarianism, justice, resourcefulness, courage, self-assurance, attention, thoughtfulness, sincerity, kindness, and politeness. President Joko Widodo effectively communicated the attributes of the four concepts of Pancasila in his speeches presented in both English and Indonesian. These speeches successfully conveyed the virtues of the four principles of Pancasila.